Effects of Microelectrólisis Percutaneous® on pain and functionality in patients with calcaneal tendinopathy. - Silva, Rodrigo Marcel Valentim da; Costa, Leandro de Souza; Coldibeli, Eloise da Silva; Fernandes, Maria do Rosário Soares; Meyer, Patrícia Froes; Ronzio, Oscar Ariel (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The Achilles tendinopathy with tendon injuries are the third most common in the musculoskeletal system. New therapies have been proposed for the treatment of tendinopathy as Percutaneous Microelectrólisis (MEP ®). Objectives: The aim of this study was to evaluate the effects of MEP ® on tendinopathy of Achilles. Method: This was a controlled clinical trial, randomized study. The sample comprised 20 patients with Achilles tendinopathy. The volunteers were randomly divided into two groups, control (G1) underwent conventional treatment protocol and experimental (G2) which was under the application of MEP. We made two visits per week for a month, totaling eight sessions. As evaluation method were used four questions from Visa-A questionnaire related to the functionality and exercise pratice. Data were analyzed using paired and independent T test. Results: The pain when walking down stairs has been observed a reduction in G1 (p <0.05) and G2 (p <0.001) before and after the protocols. Among the groups there was a greater reduction in G2 (p <0.001). Pain after heating was observed a reduction in G2 (p <0.001). Among them there was a greater reduction (p <0.05) in G2. For pain was observed after walking a reduction in G1 (p <0.05) and G2 (p <0.001) before and after the protocols. Among them there was a reduction (p <0.05) higher in G2. In pain after exercise was observed a reduction in G2 (p <0.001). Among the groups there was a greater decrease in G2 (p <0.05). Conclusion: We conclude that the MEP ® helps reduce pain in functional activities.